Pengaruh Inovasi Produk dan Harga Terhadap Keputusan Pembelian Sepeda Motor Honda Supra X 125 - Riza Fakhri Lupiko; Handojo Djoko Waloejo (Universitas Diponegoro, 2018)
Abstract The means of transportation in the present day is an important need for a human. To support human mobility today which is high, an efficient and adequate means of transportation is needed. In addition, it can accommodate daily activities. In particular, this study discusses the purchase of Honda Supra X 125 CW Astra Motor Siliwangi motorcycle. The purpose of this study was to determine the effect of product and price innovation on the purchase decision of Honda Supra X 125 CW motorcycle. This type of research uses quantitative methods with research type explanatory research, with data collection techniques through questionnaires. The population in this research are buyers and users of Honda Supra X 125 CW Astra Motor Siliwangi with the number of samples taken is 95 respondents by Slovin method. Sampling using purposive sampling technique. Analytical methods used are validity test, reliability test, classical assumption test, correlation test, determination test, simple linear regression, multiple linear regression, t-test, and F test. In this research is assisted by the computer program to process data that is SPSS. Based on the results of the study note that partially, product innovation and price have a strong relationship strong enough to the purchase decision. This is indicated by the results of the multiple correlation coefficient tests of 0.490. Significantly, the variables of product innovation and price have a positive effect indicated by the value of F arithmetic bigger than F table that is equal to 15,291>3,952. Suggestions that can be given are PT. Astra Honda Motor should make changes to the body of Honda Supra X 125 motorcycle to look fresh and keep up with the times. Also, consider the price to be more affordable or at the same price with the addition of features and technology on the Honda Supra X 125.